2008 the Third International Conference on Software Engineering Advances 2008
DOI: 10.1109/icsea.2008.8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Test Driven Development on the Evolution of a Reusable Framework of Components – An Industrial Case Study

Abstract: Test Driven Development (TDD) is a software engineering technique to promote fast feedback, taskoriented development, improved quality assurance and more comprehensible low-level software design. Benefits have been shown for non-reusable software development in terms of improved quality (e.g. lower defect density). We have carried out an empirical study of a framework of reusable components, to see whether these benefits can be shown for reusable components. The framework is used in building new applications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
(40 reference statements)
0
5
0
2
Order By: Relevance
“…As only one of the effect sizes refers to an experiment conducted in an industrial context, only the experiments from the Academic subgroup lend themselves to the standardized analysis, which results in the summary effect size of À0:049. Nevertheless, it is interesting to note that the sole industrial experiment by Slyngstad et al [63] reported a contrasting effect size of 0.309. Due to only a single industrial experiment being included in the standardized analysis, the Level 1 summary value of the Academic subgroup is not very different from the Level 0 summary value of À0:010.…”
Section: Academic Versus Industrialmentioning
confidence: 96%
See 1 more Smart Citation
“…As only one of the effect sizes refers to an experiment conducted in an industrial context, only the experiments from the Academic subgroup lend themselves to the standardized analysis, which results in the summary effect size of À0:049. Nevertheless, it is interesting to note that the sole industrial experiment by Slyngstad et al [63] reported a contrasting effect size of 0.309. Due to only a single industrial experiment being included in the standardized analysis, the Level 1 summary value of the Academic subgroup is not very different from the Level 0 summary value of À0:010.…”
Section: Academic Versus Industrialmentioning
confidence: 96%
“…Therefore, the analysis is most sensitive to, or is most effected by, the inclusion of these two experiments. Also, with the exclusion of the sole industrial study by Slyngstad et al [63], the one-study removed plot shows that the overall effect size of the 10 academic studies is approximately zero. A more detailed comparison between the effect sizes from academic and industrial studies is presented later on in the subgroup analyses.…”
Section: Standardized Analysismentioning
confidence: 97%
“…Several authors have reported that TDD is the most difficult task among the other eXtreme Programming practices [14][35] [22][36] [37]. Experienced master's level students have been reported to have difficulties with TDD [18][38] and learnign may not be easy even for experienced professional in industry [39].…”
Section: B Tdd In Curriculummentioning
confidence: 99%
“…Several studies employing XP methodology in software engineering courses have discovered TDD as the most difficult XP practice [19] [22] [12]. The difficulties have been similarly encountered by master's level students [14] and even the experienced professionals [21]. The difficulty of learning TDD arises from the demand to handle several different skills, such as test writing, testing tools, and refactoring [18].…”
Section: Tdd At Introductory Levelmentioning
confidence: 99%